The Role of Perseverative Cognition for Both Mental and Somatic Disorders in a Naturalistic Psychiatric Patient Sample. Issue 9 (November 2021) - Appel, Judith E.; Vrijsen, Janna N.; Marchetti, Igor; Becker, Eni S.; Collard, Rose M.; van Eijndhoven, Philip; Schene, Aart H.; Tendolkar, Indira
ABSTRACT: Objective: Perseverative cognition (PC) is the repeated or long-term activation of the cognitive representation of psychological stressors and is associated with prolonged stress including somatic and mental consequences. Hence, PC might represent a cognitive process linking mental and somatic pathology, but current research on this link is limited by investigating healthy samples, markers of somatic disease, and single disorders. The present study explored the importance of PC for different mental and somatic disorders in psychiatric patients. Methods: Data from 260 naturalistic psychiatric outpatients were used. Psychiatric diagnoses were based on structured clinical interviews. Somatic diseases were assessed using a well-validated questionnaire and were clustered into (cardio)vascular and immune/endocrine diseases. PC was operationalized using the Perseverative Thinking Questionnaire (PTQ). Results: Multiple regression complemented with relative importance analyses showed that the PTQ total and subscale scores were associated with the presence of mood disorders, addiction, and anxiety. Unexpectedly, no relatively important associations were found between the PTQ and autism spectrum disorder, attention-deficit/hyperactivity disorder, or somatic disease. Conclusions: Our data complement previous work linking PC to stress-related mental disorders but question its immediate role in neurodevelopmental and somatic disorders. Targeting PC in the treatment of mood disorders and perhaps also in addiction seems promising. Abstract : Supplemental digital content is available in the text.